Bismarck and the German Empire, 1871-1918 - Abrams, Lynn. (London ; New York : Routledge, 2006)
Bismarck's German Empire has been seen as a paradox, combining an advanced industrial economy and diverse social structure with an authoritarian political system. The author examines the political, economic and social structures of the Empire and the techniques employed by Bismarck to consolidate the regime.
Glossary and abbreviations -- Chronological table of events -- Map: The unification of Germany 1867-71 -- Introduction -- The new German state -- Bismarck and consolidation 1871-90 -- Confrontation and integration 1890-1914 -- War and revolution 1914-1919 -- Interpretations.
Includes bibliographical references (pages 85-89) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Bismarck, Otto, -- Fürst von, -- 1815-1898.; Bismarck, Otto, -- Fürst von, -- 1815-1898; Statesmen -- Germany -- Biography; Germany -- Politics and government -- 1871-1918.; Hommes d'État -- Allemagne -- Biographies; Allemagne -- Politique et gouvernement -- 1871-1918.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY; Politics and government; Statesmen; Germany; 1871-1918; Electronic books; Biographies; Biographies; Biographies